Cecal microbiota of broilers responds similarly to black soldier fly larvae fat and conventional dietary fat sources - Muhammad Rumman Aslam; Bartosz Kierończyk; Piotr Szymkowiak; Liliana Ciesielska; Mateusz Rawski; Robert Mikuła; Damian Józefiak (PLoS ONE, 2025)
This study aimed to compare the effects of black soldier fly ( Hermetia illucens ) larvae (BSFL) fat with those of dietary fats commonly used in broiler chicken nutrition on gut pH and cecal microbiome. A total of 800 one-day-old male Ross 308 chicks were randomly assigned to eight dietary groups, with each group consisting of 10 replicate pens of 10 birds each fed for 35 days. The study design was as follows: the basal diet was enriched with various dietary fats as the sole source of fat, including BSFL fat (as the reference group), soybean oil (SO), rapeseed oil (RO), palm oil (PO), palm kernel fatty acid distillate (PKFD), poultry fat (PF), pig lard (PL), and beef tallow (BT). At the end of the experiment (35 days), the digesta from the crop, gizzard, jejunum, and ceca were sampled for further analyses, including pH determination and next-generation sequencing (NGS). Compared with PKFD, PF, and BT, BSFL significantly reduced the crop pH (P = 0.005). Additionally, BSFL increased the gizzard pH (P = 0.006) relative to PKFD. No differences in alpha diversity were detected among the diets; however, beta diversity differed significantly between the BSFL and PKFD groups (P = 0.034). BSFL fat was associated with a significant reduction in the abundances of Proteobacteria (P = 0.011), Enterobacteriaceae (P = 0.009), and Escherichia-Shigella (P = 0.009) compared with PKFD fat. LEfSe analysis revealed the following microbial markers responsive to BSFL treatment: total bacteria (P < 0.001), Rikenellaceae (P = 0.025), Peptococcaceae [uncultured genus] (P = 0.003), Rhodospirillales (P = 0.048), Alistipes (P = 0.025), the Eubacterium coprostanoligenes group (P = 0.018), the Clostridia vadin BB60 group (P = 0.032), and Alistipes sp. (P = 0.023). These findings suggest that BSFL positively affects the pH in the upper part of a bird’s gut compared with selected animal fats. Furthermore, BSFL enriched beneficial bacteria while inhibiting opportunistic pathogens in the cecal environment of broiler chickens.